2017
DOI: 10.1364/oe.25.031552
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive detection of voltage transients using differential intensity surface plasmon resonance system

Abstract: Sensitive detection of voltage transients using differential intensity surface plasmon resonance system. Optics Express, 25 (25). pp. 31552-31567. ISSN 1094-4087 Access from the University of Nottingham repository: http://eprints.nottingham.ac.uk/46901/8/oe-25-25-31552.pdf Copyright and reuse:The Nottingham ePrints service makes this work by researchers of the University of Nottingham available open access under the following conditions. This article is made available under the Creative Commons Attribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…This 47 nm gold sensor was then calculated for different applied voltage levels as shown in Figure 7 b. The responses here agree very well with the results reported in Abayzeed et al [ 16 ]. The results in Figure 7 b allows us to calculate the defined performance parameters as shown in Figure 8 .…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…This 47 nm gold sensor was then calculated for different applied voltage levels as shown in Figure 7 b. The responses here agree very well with the results reported in Abayzeed et al [ 16 ]. The results in Figure 7 b allows us to calculate the defined performance parameters as shown in Figure 8 .…”
Section: Resultssupporting
confidence: 86%
“…Recently, there has been an interest in employing label-free detection using surface plasmon resonance (SPR) as a voltage sensing platform for biological samples [ 15 , 16 , 17 , 18 , 19 ]. The SPR has been a gold standard for real-time binding kinetics studies [ 20 ] and very low concentration biological measurements [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our observations suggested that we could wirelessly drive redox chemistry via the application of an electrical field at a low potential difference that was orders of magnitude lower to that reported at other nanostructures, such as carbon nanotubes (CNTs) 16 . To further prove our hypothesis that redox reactions could be triggered at relatively low voltage, we explored an alternative label-free approach based on the voltage sensitivity of plasmonic nanostructures [26][27][28][29][30][31] .…”
mentioning
confidence: 99%
“…In a typical dielectric medium such as air, an external field can modulate plasmonic resonances by changing the carrier density n e of the PNA within a skin depth at the surface, known as Thomas-Fermi screening length [157,194,195]. Depending on the direction of the applied electric field, carrier density Δn e increases (decreases) due to charge accumulation (depletion) at the surface [196,197]. This free-carrier density variation results in alteration of the plasma frequency ω p .…”
Section: Electrical Gatingmentioning
confidence: 99%